The Inability to Take Responsibility of Paranoid Schizophrenic Criminal Perpetrators and Its Implications for the Protection of Victims' Rights from the Pancasila Perspective - Sri Budi Raharjo; Hartiwiningsih; Ismunarno (Journal of Legal and Cultural Analytics, 2026)
Criminal acts committed by individuals with paranoid schizophrenia present significant challenges within the criminal justice system. Due to their mental condition, offenders are often considered incapable of criminal responsibility and are directed toward medical rehabilitation rather than criminal punishment. Consequently, victims’ rights, including compensation, psychological recovery, and access to justice, are frequently overlooked. This study aims to analyze the implications of the offender’s inability to assume criminal responsibility on the protection of victims’ rights from the perspective of Pancasila. The research employs a normative legal method using statutory, conceptual, and philosophical approaches. Primary legal materials include the Criminal Code, the Health Law, and the Human Rights Law, supported by relevant literature and legal doctrines. The findings indicate that existing legal regulations place greater emphasis on offender rehabilitation, resulting in inadequate protection of victims’ rights. From the perspective of Pancasila, particularly the principles of Just and Civilized Humanity and Social Justice for All Indonesian People, victim protection constitutes an essential element of justice and human dignity. Therefore, criminal law reform is required to balance offender rehabilitation with victim protection through compensation mechanisms, restorative justice, and stronger institutional coordination, thereby creating a more equitable criminal justice system based on Pancasila values.